(untitled) (Bangladesh Journal of Botany, 2020)
Twenty exotic pomegranate (Punica granatum L.) germplasms were studied to determine the genetic parameters to understand the usefulness of genotypes in the breeding program. Forty characteristics were measured in fruits, arils, leaves, and flowers, as well as juice characteristics including, total soluble solids, titratable acidity, sugars, anthocyanin, and phenols. Analysis of variance establishes that among all the parameters analyzed, a significant genetic difference was present for yield and yield attribution traits of the studied pomegranate germplasm. All plants were grouped into five clusters among them Green Globe and Hakubotan were most distinct from others. Saharnyi, Orange, Ovadan, Nusai, Kaim-anar, Al-Sirin-Nar, 20090265, Eve and Sogdiana may be used as one of the parent with another parent Green Globe for getting better recombinants by hybridization method. The presence of significant inter-cluster variations revealed that hybridization program could be useful for the development of better plant type by using this pomegranate germplasms. Factor analysis exhibits that fruit weight shown to have the highest different value in the tested pomegranate germplasms so that this trait can be used for the separation and selection of pomegranate germplasms.